Artificial Intelligence in Arabic Language Learning: A Systematic Review of Adaptive Learning, Natural Language Processing, Speech Recognition, and Implementation Challenges in the Digital Era - Anugrah Ilahi; Muhammad Fitriyadi (Penerbit Minhaj Pustaka, 2026)
This study examines the role of artificial intelligence (AI) in the development of Arabic language learning in the digital era. The rapid advancement of AI technology has opened new opportunities to enhance the quality and effectiveness of Arabic language instruction, both in formal educational settings and independent learning environments. Using a qualitative approach with a literature review method, this research analyzes various AI-based applications and platforms currently used in Arabic language learning, including chatbot-based language tools, speech recognition applications, adaptive learning systems, and natural language processing (NLP) technologies. The findings reveal that AI contributes significantly to personalized learning experiences, real-time pronunciation feedback, intelligent vocabulary acquisition, and interactive Arabic script recognition. However, several challenges remain, including limited Arabic language datasets, inadequate digital infrastructure in developing countries, and the need for trained educators to integrate AI effectively into curricula. This study concludes that AI holds great potential to transform Arabic language education, and recommends collaborative efforts among educators, technology developers, and policymakers to maximize its benefits.